Introduction: Indigenous Futurisms in the hyperpresent now. Issue 2 (4th May 2019) - Fricke, Suzanne Newman
Abstract : Introduced less than two decades ago, Indigenous Futurisms envisions the future from an Native perspective in fiction and in visual arts. Usually described through the disciplines of anthropology, cultural studies, and comparative literature, scholars including Grace Dillon, Jason Lewis, William Gaertner, and William Lempert, have explored the concept. As it has moved more and more into the visual arts, scholarship from an art historical approach is necessary. Through Indigenous Futurisms, artists including Sonny Assu, Andy Everson, Suzanne Kite, Ryan Singer, Skawennati, Hoka Skenandore, Jeffrey Veregge, and Debra Yepa-Pappan have addressed a range of difficult topics, including the long impact of colonization, institutional racism, destruction of the environment, and genocide. While many of these artists work in historic media such as painting, drawing, beadwork, and photography, the field encourages artists to explore new media including digital art, virtual reality, and websites. This essay consider the term "Indigenous Futurisms" and its impact of the field of visual culture and art history.